2021
DOI: 10.5604/01.3001.0014.7974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of targeted physiotherapy on the quality of life of patients with epilepsy of unknown etiology – a pilot study

Abstract: Introduction: Epilepsy is one of the most common diseases of the central nervous system. According to the World Health Organization, it accounts for 1% of the global burden of disease worldwide. Pharmacotherapy remains the primary therapeutic tool in this disease. However, more and more emphasis is placed on approaching this group of patients in an interdisciplinary manner, taking their various needs into account: social, professional, economic or psychological. Attention is also paid to the positive impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“… [54] single-group multidisciplinary program consisting of cognitive rehabilitation, physical fitness and motor coordination exercises, therapeutic counseling to improve disease coping, educational sessions, mindfulness training, and legal advice 1.5 hr/day across all modules for an average of 11 inpatient days any 1,339 14–87 compliance, affect/mood, activity, communication, mobility/physical fitness, fine motor skills, autonomy/independence from assistance (observer-rated) intervention improved compliance, activity, affect, and total impairment no Szczygieł-Pilut et al, 2020. [77] single-group crossover (controlled) physiotherapy focused on balance training 2 30-min sessions/week over one month baseline/no intervention (two months wait pre-intervention) generalized epilepsy of unknown etiology, controlled with ASM 10 18–65 years QOL physiotherapy improved QOL in domains of physical functioning, physical limitations, pain, vitality, social functioning, mental health, emotional functioning, and total QOL no Vooturi et al, 2020. [78] RCT moderate-intensity home-based aerobic (cardiovascular, endurance, flexibility) exercise at 60 % target heart rate 4 45-min sessions/week over 12 weeks education only, continue existing exercise programs controlled (seizure-free for two years, on ASM) exercise, 48; control, 42 18–60 weight, BMI, abdominal, waist, and hip circumference, physical capacity, QOL, metabolic markers exercise reduced weight and improved physical capacity and physical QOL sleep duration reported only at baseline Vooturi et al, 2023.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [54] single-group multidisciplinary program consisting of cognitive rehabilitation, physical fitness and motor coordination exercises, therapeutic counseling to improve disease coping, educational sessions, mindfulness training, and legal advice 1.5 hr/day across all modules for an average of 11 inpatient days any 1,339 14–87 compliance, affect/mood, activity, communication, mobility/physical fitness, fine motor skills, autonomy/independence from assistance (observer-rated) intervention improved compliance, activity, affect, and total impairment no Szczygieł-Pilut et al, 2020. [77] single-group crossover (controlled) physiotherapy focused on balance training 2 30-min sessions/week over one month baseline/no intervention (two months wait pre-intervention) generalized epilepsy of unknown etiology, controlled with ASM 10 18–65 years QOL physiotherapy improved QOL in domains of physical functioning, physical limitations, pain, vitality, social functioning, mental health, emotional functioning, and total QOL no Vooturi et al, 2020. [78] RCT moderate-intensity home-based aerobic (cardiovascular, endurance, flexibility) exercise at 60 % target heart rate 4 45-min sessions/week over 12 weeks education only, continue existing exercise programs controlled (seizure-free for two years, on ASM) exercise, 48; control, 42 18–60 weight, BMI, abdominal, waist, and hip circumference, physical capacity, QOL, metabolic markers exercise reduced weight and improved physical capacity and physical QOL sleep duration reported only at baseline Vooturi et al, 2023.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 studies reported by 23 articles, four (4) exclusively used cardiovascular/aerobic training without a strength component. Two studies (three publications) from Canada assessed the effects of daily walking [49] , [50] , [51] , one study each tested yoga [52] and balance training [53] , and two studies did not report enough detail to determine the type of exercise or used different modalities for each participant [54] , [31] . Finally, one study tested yoga against “simple exercise” training [55] , so both intervention arms could be considered exercise interventions for the purposes of this review.…”
Section: Resultsmentioning
confidence: 99%